PENGEMBANGAN BLANDED LEARNING MATA KULIAH BILANGAN DAN PENGOLAHAN DATA UNTUK MAHASISWA PGSD - Delia Indrawati (Universitas PGRI Adi Buana Surabaya, 2019)
Applying science and technology in the lecture process can be done by applying blended learning, namely offline and online. Technology adaptation must be immediately familiarized for students and lecturers to optimize the effectiveness of lectures. This study describes the development of blended learning in number lectures and data processing and the feasibility of developing and knowing student responses after attending lectures. Development research using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Design of lecture meetings with seven online and eight face-to-face meetings. Data were obtained from material and media validation instruments and student response questionnaires. The research subjects were 39 students of class D Class 2018. The percentage of the score analyzed the data obtained divided by the maximum score multiplied by 100%. The development of blended learning is arranged at LMS Unesa. Expert lecturers validate the materials and media in the LMS with the available position of lector and in charge of mathematics courses in the PGSD major. The results of the media validation test were 84%, and the material validation was 96%, with a very valid category. The student's questionnaire response was 95% in the very good category. The results of this development research were declared feasible with a few revisions and were effective for student lectures.